Уманщина в 1918 – 1919 гг.: война, настроения, жизненная стойкость = Umanshchina v 1918 – 1919 gg.: voyna, nastroyeniya, zhiznennaya stoykost’ - ПОСАДСКИЙ, Антон (Historia i Świat, 2019)
The article combines the quality of analytical and documentary materials. It is based on the meaningful memories of the witness of the events of the civil war in 1918 – 1919 in the Uman district of the Kiev province. The view of the non-politicized witness and participant is of particular value. The correction of the proposed point of view is carried out with the help of comments, which use both published and unpublished sources.